CAN DRAMA LESSONS BE GIVEN ONLINE?: PERSPECTIVES OF DRAMA TEACHERS DURING THE COVID-19 - Karaosmanoğlu, Gökhan; Adıgüzel, Ömer; Metinnam, İhsan; Özen, Zeki (International Online Journal of Education and Teaching, 2022)
In the COVID-19 pandemic, people's opportunities for face-to-face education have been limited, and the way they access educational content has changed. During the pandemic, both institutions providing drama lessons and drama instructors had the opportunity to rethink drama education and adapt drama studies in different ways. During the pandemic, different opinions emerged about whether creative drama classes should continue if they continue, what changes will be made in drama studies, drama education programs, and which applications will be used. This research aims to determine the changes in drama lessons during the COVID-19 pandemic, the digital platforms where online drama lessons are held, and the Web 2.0 tools used by taking the opinions of drama teachers. The interpretive qualitative research design was used in the study. The Online Drama Lessons Evaluation Form was used as a data collection tool to determine the opinions of drama teachers working in private or public institutions. 58 drama teachers answered the form. The qualitative data in the research were analyzed by descriptive analysis, the findings were first coded line by line, and the common codes were classified under appropriate categories and themes. According to the results of the research, it can be said that the drama teachers adapted the drama education programs by social distance (face-to-face studies) and transformed the drama activities to be applied on digital platforms. It can be said that the necessary changes were made in the drama activities and the drama education program while giving the drama lessons online, and the Zoom digital platform was mainly used in the online lessons. Drama teachers stated that they used Web 2.0 tools such as Padlet, Menti, Kahoot to evaluate online lessons, get or give feedback, and determine readiness/preparedness.